VERSE IN THE MIDST OF GAZA: Finding Love In Religious Texts During The Humanitarian Crisis In Palestine - Nugroho; Taufiqurrahman; Trilipi, Desi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines how the concepts of love (mahabbah) and compassion (rahmah) in religious texts, particularly the Qur'an and the Bible, can be reactualized as the foundation of an ethic of solidarity amidst the humanitarian crisis in Gaza. The protracted crisis in Gaza demonstrates the irony of how religion is often used to justify conflict, even though it contains the teachings of universal love. Using the hermeneutics of love, liberation theology, and ethics of empathy, this study explores how verses about mercy and agape have transformed into practices of interfaith solidarity, ranging from donation drives and communal prayer to advocacy for justice. It also highlights the challenges of the politicization of religion and narratives of hatred that hijack sacred texts for the sake of power. The results of this study emphasize that rediscovering verses about love can serve as a foundation for a global ethic for caring for humanity amidst the wounds of Gaza. Religion, ultimately, is not merely an identity, but a bridge that embraces all of humanity. Keywords: Agape, Gaza, Hermeneutics, Mercy, Solidarity